Systems theory, systems art and the computer: Ernest Edmonds interviewed by Francesca Franco. (3rd April 2017) - Edmonds, Ernest; Franco, Francesca
ABSTRACT: This interview with Edmonds, conducted by Franco in 2016, explores how Systems art, Systems Theory, and his personal relationships with artists such as Malcolm Hughes, Kenneth Martin and Edward Ihnatowicz influenced his art practice.